La percezione corporea tra pieghe ed interstizi: Nota sulla fenomenologia dell’esperienza estetica - De Caro, Eugenio (Scenari, 2021)
What is actually a sensation? The sensation’s data are mere empirical inputs whose significance refers exclusively to their decoding by the central nervous system, or they are functions “originally” involved in a process of signification / understanding of reality, process which must be taken into account from the beginning of their becoming “matter of facts”? The paper aims to set up an answer to this question. Keeping on the background the notion of "fold" as proposed by Gilles Deleuze, the question of bodily perception is analysed considering its framing in the nascent modern physiology by the English physician Francis Glisson (later exploited by Leibniz) according to which there is no solution of continuity between body and mind (or soul). Body and mind do not represent two different types of substance, as they differ only in terms of clarity and self-transparency. This conception is in line with the notion of corporeity proposed by Deleuze, where the body interacts with outside forces by deforming and forming folds inside itself, while consciousness works exclusively on the emerging margins of those folds. Francis Bacon's painting should then try to explain this sensation and perception model and the notion of “landscape” as opposed to the “geography” proposed by Erwin Straus is another interesting variation of it.